Distinguishing between Traditional and Online Retailing: Evaluating E-commerce with Respect to the Food System - Angelina C. Toomey; Allen F. Wysocki (EDIS)
FE820, a 4-page fact sheet by Angelina C. Toomey and Allen F. Wysocki, focuses on business-to-consumer (B2C) practices, and in particular, B2C methods of e-commerce with respect to online food sales. Includes references. Published by the UF Department of Food and Resource Economics, December 2009.